PERADILAN RESTORATIF SEBAGAI ALTERNATIF DALAM SISTEM PERADILAN PIDANA (Pendekatan Analisis Komparatif Sistem) - S. Sahabuddin S. Sahabuddin (Jurnal LEX SPECIALIS, 2012)
Abstract Restorative Justice utilizing three elements (perpetrators, victims, and society) as a system that works to restore a state that has been damaged due to the occurrence of a particular crime. The essence of restorative justice lies in the value of the deal (commitment) between the parties to remedy the situation as before. Is not the purpose of enforcement of the criminal law is a just satisfaction in a certain state (rule of law). restorative justice in relation to the goal of creating a participatory process to discuss the blameworthiness of the victim, and this can be achieved by utilizing local laws that were able to neutralize the situation. In the development of the legal system in the world, we recognize two major legal systems are very different from each other in the lead and provide guidance to the working parts, the second system is a civil law legal system, or often said as the Continental European legal systems, and then one is the common law system, or often called the anglo-saxon system that comes from living law. Both the legal system is characterized, mechanisms and goals of each and have a history of birth is influenced by societal values nationality respectively. Here's a comparison of the two legal systems characterize the status or position of restorative justice more in line with the common law system / anglo saxon, because justice is mengendepankan repair using or utilizing the law of life in the community (living law), while living law itself was basic implementation of the common law. Key Note : Restorative Justice, Criminal Justice System